Characterization of a Candidate bcl-1 Gene - Withers, Donald A.; Harvey, Richard C.; Faust, John B.; Melnyk, Ostap; Carey, Kendall; Meeker, Timothy C. (Molecular and cellular biology, 1991)
The t(11;14)(q13;q32) translocation has been associated with human B-lymphocytic malignancy. Several examples of this translocation have been cloned, documenting that this abnormality joins the immunoglobulin heavy-chain gene to the bcl-1 locus on chromosome 11. However, the identification of the bcl-1 gene, a putative dominant oncogene, has been elusive. In this work, we have isolated genomic clones covering 120 kb of the bcl-1 locus. Probes from the region of an HpaII-tiny-fragment island identified a candidate bcl-1 gene. cDNAs representing the bcl-1 mRNA were cloned from three cell lines, two with the translocation. The deduced amino acid sequence from these clones showed bcl-1 to be a member of the cyclin gene family. In addition, our analysis of expression of bcl-1 in an extensive panel of human cell lines showed it to be widely expressed except in lymphoid or myeloid lineages. This observation may provide a molecular basis for distinct modes of cell cycle control in different mammalian tissues. Activation of the bcl-1 gene may be oncogenic by directly altering progression through the cell cycle.